Tingkat Adopsi Petani pada Penggunaan Teknologi Biofarm (Studi Kasus Petani Padi Organik GAPOKTAN Sulek Raya Kabupaten Bondowoso) - Suryandari, Ayu; Mazwan, M. Zul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Organic rice cultivation in Indonesia has experienced rapid development due to increasing healthy lifestyle patterns among the population, yet faces various constraints such as limited availability of organic fertilizers and biopesticides. This research aims to evaluate the level of farmer adoption of biofarm technology as a solution in organic rice cultivation. This study was conducted using a qualitative approach whereby data were obtained through offline questionnaire distribution to 30 respondents who participated in the biofarm technology pilot program. Sampling was conducted using census technique, and the obtained data were analyzed statistically using descriptive analysis and Structural Equation Modeling based on Partial Least Square (SEM-PLS) method. Results showed that mentoring effectiveness (X1) positvely influenced the level of biofarm tecnology adoption with a path coefficient of 0,51, while farmes’ technological readiness (X2) had no significant effect and teknological advancement (X3) has a significant influence with a path coefficient of 0,38. Overall, the three independent variabels explained 43% of the variation in farmers’ innovation adoption levels regarding biofarm technology. This research recommends the importance of farmers’ consistency in using biofarm tecnology to overcome fertilizer and biopesticide scarcity, as well as government support through policies and incentives for organic rice rafmers.